Development of Artificial Intellegence-Based Akidah Akhlak Teaching Materials for Islamic Senior High Schools in Indonesia - Rofiatul Hosna; Khoirotul Idawati; Hanifudin Hanifudin; Ali Mahsun; Erika Mei Budiarti; Iva Inayatul Ilahiyah; Mustaji Mustaji (Nazhruna: Jurnal Pendidikan Islam, 2026)
The rapid development of technology, particularly Artificial Intelligence (AI), has opened new opportunities to enhance the quality of education, including Islamic religious education. The Akidah Akhlak subject is still predominantly taught using conventional methods, which are often monotonous and less engaging for the digital generation. Therefore, there is a need for innovative, interactive, and adaptive teaching materials. This study aims to develop AI-based teaching materials to improve student engagement, understanding, and learning outcomes in Akidah Akhlak. This research employs a Research and Development (R&D) approach with both qualitative and quantitative designs. The ADDIE model (Analyze, Design, Develop, Implement, Evaluate) is applied to develop the teaching materials, supported by the Quizizz platform as an interactive tool for learning and formative assessment. Data were collected through interviews, observations, documentation, pre-tests and post-tests, and student questionnaires, then analyzed using thematic analysis for qualitative data and statistical tests for quantitative data. The results indicate that the AI-based teaching materials are highly feasible, with expert validation reaching 84% and student response at 83%. Pre-test and post-test analyses showed a significant improvement in student understanding, with the average N-Gain score increasing from 53.16 to 81.53, demonstrating high effectiveness. The findings imply that AI-based teaching materials not only enhance the quality of Akidah Akhlak learning but also provide an interactive teaching alternative that aligns with the needs of the digital generation. This study serves as a reference for Islamic educational institutions in leveraging technology to enrich students’ learning experiences.